2014
DOI: 10.1210/jc.2013-2376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing Glutathione With Cysteine and Glycine Supplementation on Mitochondrial Fuel Oxidation, Insulin Sensitivity, and Body Composition in Older HIV-Infected Patients

Abstract: This work identifies 2 novel findings in older HIV-infected patients: 1) diminished synthesis due to decreased availability of cysteine and glycine contributes to GSH deficiency and can be rapidly corrected by dietary supplementation of these precursors and 2) correction of GSH deficiency is associated with improvement of mitochondrial fat and carbohydrate oxidation in both fasted and fed states and with improvements in insulin sensitivity, body composition, and muscle strength. The role of GSH on ameliorating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 35 publications
6
75
0
2
Order By: Relevance
“…Redox signals are critical regulators of HIV replication, immune dysfunction, and disease progression (55, 56). Altered energy balance is consistent with studies showing loss of mitochondrial membrane potential, increased production of reactive oxygen species (ROS), and depletion of major intracellular antioxidants, glutathione, and thioredoxin in HIV infection (57). …”
Section: Regulation Of Immune Cell Metabolism By Oxidative Stress Andsupporting
confidence: 85%
“…Redox signals are critical regulators of HIV replication, immune dysfunction, and disease progression (55, 56). Altered energy balance is consistent with studies showing loss of mitochondrial membrane potential, increased production of reactive oxygen species (ROS), and depletion of major intracellular antioxidants, glutathione, and thioredoxin in HIV infection (57). …”
Section: Regulation Of Immune Cell Metabolism By Oxidative Stress Andsupporting
confidence: 85%
“…It has been shown that the requirements for glycine and cysteine are increased in inflammatory situations [34,35], and dietary supplementation with GSH precursor amino acids cysteine and glycine can restore GSH synthesis and alleviate oxidative stress in patients with uncontrolled diabetes [12], ageing [36], Parkinson's disease [34], HIV-infected patients [37], also in rats and broilers fed with low protein diets [35,38]. It seems that in some inflammatory situations, the protein turnover may have been impaired and the de novo synthesis rate of cysteine and glycine, could not meet the demand for sufficient GSH synthesis [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…GSH is a physiological antioxidant, a co‐factor of many enzymes, and plays an important role in a multitude of cellular processes. LC can also have a direct effect on post‐translational modification or S‐glutathionylation of proteins, which can cause modification of structure and function and thereby provide protection against oxidative signaling events . Elevated oxidative stress in various tissues from uncontrolled hyperglycemia may cause increased LC utilization and the lower levels seen in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating and tissue levels of glutathione (GSH) decrease with age, and in chronic diseases such as diabetes . GSH is a co‐factor of many enzymes, a potent antioxidant, and plays an important role as a scavenger of toxic oxygen radicals, which helps to maintain normal cell functions . Vitamin D binding protein (VDBP) is a main transporter of vitamin D and 25(OH) vitamin D .…”
Section: Introductionmentioning
confidence: 99%